Authorial Voice in Academic Articles: A Corpus-Based Analysis of Citation Types and Citation Presentation across Disciplines - Hanks, Elizabeth; Eckstein, Grant; Rawlins, Jacob; Briggs, Haley; Chun, Leanne (Journal of Academic Writing, 2024)
Authorial voice plays a key role in helping writers establish themselves as experts in their field as well as demonstrate their individual style (e.g., Tardy, 2012). Citation usage has an important impact on authorial voice in academic writing and can be implemented in various ways; namely, through citation types (e.g., integral, non-integral) and citation presentation (e.g., direct quotes, summaries, generalizations). While many researchers have examined citation type among novice and experienced writers, researchers have largely overlooked citation presentation across disciplines – that is, how experienced authors balance the use of quotations, summaries, and generalization to index authorial voice. Beginning academic writers may be encouraged to use quotations to prevent plagiarism, but it is unclear if this advice reflects patterns in published writing across disciplines. In this study, we examine the background sections (i.e., introductions and/or literature reviews) of 270 academic research papers to evaluate the extent to which various citation types and presentations are used in background sections across six disciplines. Findings which can inform disciplinary writing guides and educational materials indicate disciplinary variation in citation type, with applied linguistics using the most citations overall and physics and biology using the fewest integral citations. Disciplines also differed in their citation presentation, with some favoring summaries and others favoring generalizations while quotation was rare overall. These results have important implications for teachers and material developers who can use these patterns of source usage to compare and contrast disciplinary norms and provide direct instruction on features of academic voice. Cross-disciplinary awareness of voice features can also highlight disciplinary patterns for students, allowing them to write more like experts in their fields.